(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The rapid growth of Information and Communication Technology (ICT) has revolutionized various sectors, including agriculture. In rural India, ICT tools are emerging as key enablers for disseminating agricultural knowledge and practices. However, the adoption of these tools is hindered by socio-economic, infrastructural, and digital literacy challenges, creating a digital divide. This study examines the adoption trends, benefits, and challenges of ICT tools in agriculture in rural India. A mixed-methods approach was used, involving surveys with 500 farmers across five states and in-depth interviews with extension agents and ICT service providers. Findings indicate that while ICT tools have improved market access, productivity, and decision-making, barriers such as low literacy levels, limited infrastructure, and gender disparities persist. Recommendations include investing in digital literacy, enhancing infrastructure, and tailoring ICT solutions to local needs to ensure equitable access.